How and why do educational psychology services engage with an ACE-informed approach?. Issue 4 (2nd October 2021) - Shaw, Beth; Woods, Kevin; Ford, Anne
ABSTRACT: Adverse childhood experiences (ACEs) and related approaches are receiving increasing focus from education policy makers and educational psychologists. However, the extent to which ACEs research and theory can be used to inform practice continues to be a topic for debate. The present paper explores the development of ACE-informed practice within two UK local authority educational psychology services, through use of focus groups and interviews with educational psychologists. Rationale, facilitators and barriers to the development of current ACE-informed practice are reported. Implications for educational psychology practice, including consideration of risk and reliance factors, the importance of consistent implementation of approaches, and future research are also considered.